2022
DOI: 10.3389/fpubh.2022.922385
|View full text |Cite
|
Sign up to set email alerts
|

Recent HIV infection among newly diagnosed cases and associated factors in the Amhara regional state, Northern Ethiopia: HIV case surveillance data analysis (2019-2021)

Abstract: BackgroundDistinguishing a recent from long-standing HIV infection is a critical step to reduce new infections in 2030. Therefore, this analysis determines the proportion of recent HIV infections among newly diagnosed cases and associated factors in the Amhara regional state between 2019 and 2021.MethodsWe got the HIV case-based surveillance dataset (July 2019 up to August 12/2021) from the Amhara Public Health Institute. Recent infection is an infection gained within the last 12 months as identified by Asante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 10 publications
(12 reference statements)
3
10
0
Order By: Relevance
“…Seven facilities lacked functional generators for power backup and facilities that had functional generators faced fuel shortages. Our ndings were consistent with those who found that some of the challenges in the HIV CBS system were electricity outages and a lack of supplies to operate the system (12,13).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Seven facilities lacked functional generators for power backup and facilities that had functional generators faced fuel shortages. Our ndings were consistent with those who found that some of the challenges in the HIV CBS system were electricity outages and a lack of supplies to operate the system (12,13).…”
supporting
confidence: 91%
“…Hence, evaluation of a surveillance system is vital in the identi cation of gaps in the system as well as ensuring improvement in the quality, e ciency, and usefulness of the system. (4) This evaluation sought to answer the following questions: What are the operations, functionality and attributes of the HIV surveillance system in Dire Dawa? (5)…”
mentioning
confidence: 99%
“…However, paradoxically, HIV infection rates are higher in urban areas. Similarly, individuals primary, secondary and higher education levels were at a higher risk of HIV infection [ 42 ], despite having better knowledge, attitudes, and testing related to HIV compared to those with no formal education [ 26 28 ]. This may contribute to the misunderstanding of equity in health care services.…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopia comprises 10 regions and two administration cities, one of which is the Amhara region where HIV infection is observed. Between 2019 and 2021, out of 3,129 individuals who underwent HIV testing in some parts of Amhara region, 14.2% tested positive for HIV [ 42 ]. Based on wealth quantile in 2016, the distribution in the Amhara region was as follows: 16.4% poorest, 21.0% poorer, 22.7% middle, 22.9% richer, and 17.0% richest.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral and technical factors such as poor documentation practice, skill gap, and lack of experience which result in poor data quality and poor information utilization for decision-making were the other challenges for the surveillance system in Ethiopia. Moreover, the challenges to the surveillance of low-and middle-income countries including Ethiopia are limited resources, both fnancial and capacitated human resources [41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%